Fast decomposition of food waste to produce mature and stable compost - Ika Bagus Priyambada; Irawan Wisnu Wardana (Center for Science and Technology, IAIN Surakarta, 2018)
Food waste can be meat, fish, cooked food scraps, moldy bread, bone scraps, cakes, expired foods, dairy products, fruits and vegetables. Food waste which is put into the trash will decay and produce a foul odor which in turn will invite flies and cause potentially diseases. Most of the food waste that is processed using the composting process needs to spend a relatively long time, which is about 1-3 months or even 6-12 months. This study aims to accelerate composting time through the addition of additive microorganisms in various quantities. Four aerobic composter reactors were utilized in this study. Variations of additive microorganisms added to the research object were 0 in reactor (control), 8 g in B2 reactor, 16 g in B3 reactor, and 32 g in B4 reactor. All reactors were added with dolomite lime. During the composting process temperature, pH, water content and macroelement were tested. The results showed that the mature and stable compost was reached on the seventh day and produced from B2 reactor. In That reactor treated food waste and additive microorganisms with a ratio of 7:3, and 1 g dolomite lime. The level of C/N ratio produced from B2 reactor was 16.71. The value of C/N ratio was better than B3 reactor which produced C/N of 18.37. The control reactor produced a C/N ratio of 21.84 and mature and stable compost was reached on the 14th day. All in all, this study was regarded to be successful in accelerating the degradation of food waste into mature and stable compost in just seven days.